Understanding Bachelorhood in Poverty-stricken and High Sex Ratio Settings: An Exploratory Study in Rural Shaanxi, China. (11th April 2019) - Attané, Isabelle; Eklund, Lisa; Merli, M. Giovanna; Bozon, Michel; Angeloff, Tania; Yang, Bo; Li, Shuzhuo; Pairault, Thierry; Wang, Su; Yang, Xueyan; Zhang, Qunlin
Abstract: Coupled with the social practice of female hypergamy, the male surplus within the never-married population means that today's Chinese marriage market is extremely tight in particular for men from a rural background and the least privileged socio-economic categories. Drawing on quantitative data from a survey conducted in 2014–2015, this article sheds light on the situation of single men who are past prime marriage age in three rural districts of Shaanxi particularly affected by this phenomenon. It compares single men's characteristics to those of their married counterparts and offers insights into the heterogeneity of single men with the aim of challenging some commonly accepted assumptions about bachelorhood in rural China. Results suggest a strong internalization of the various characteristics, centred on being able to offer social mobility to a potential wife, that a man is expected to have to be attractive to women in a context where women have more choice in mate selection. We conclude that mate selection is highly marked by class, social norms, social interactions, health, generation and age, and requires the mobilization of certain amounts of individual, social and economic resources. Unwanted bachelorhood would thus be better understood using an intersectional approach rather than mainly in numeric terms. 摘要: 由于女性择偶向上选择等社会因素，单身男性的数量过剩已让中国婚姻市场十分紧张，尤其是对那些出身农村和处于社会经济劣势地位的男性而言，这一现象更是突出。根据 2014–2015 年展开的量化调查资料，本文试图以接受调查的陕西三县农村地区、超过普遍初婚年龄的单身男性为研究对象，阐明他们的处境。本文对比了单身男性和已婚男性的分别特征，展示了他们之间的差异，提出了一些与中国农村单身现象通常假设相悖的看法。研究结果表明在女性能够更宽泛选择配偶的背景下，男性内在化社会男性期待（主要指男性需为女性提供通过婚姻实现向上社会流动的条件和契机）的倾向十分强烈。我们认为，对配偶的选择与阶层、社会规范和社会互动方式、健康条件、代际和年龄等都密切相关，而且意味着对一定数量个人社会经济资源的动用。因此，比起以数据观察为主的单纯视角，多元交叉视角能让我们更好理解"非自愿"单身现象。